Virtuous Decision Making for Business Ethics - Provis, Chris (Journal of business ethics, 2010)
In recent years, increasing attention has been given to virtue ethics in business. Aristotle’s thought is often seen as the basis of the virtue ethics tradition. For Aristotle, the idea of phronēsis, or ‘practical wisdom’, lies at the foundation of ethics. Confucian ethics has notable similarities to Aristotelian virtue ethics, and may embody some similar ideas of practical wisdom. This article considers how ideas of moral judgment in these traditions are consistent with modern ideas about intuition in management decision making. A hypothetical case is considered where the complexity of ethical decision making in a group context illustrates the importance of intuitive, phronēsis-like judgment. It is then noted that both Aristotelian and Confucian virtue ethics include suggestions about support for moral decision making that are also consistent with modern theory.